Erythrocyte Complement Receptor 1 Gene Polymorphisms and Neonatal Respiratory Distress Syndrome - Rabie, Walaa; Al-Taweel, Ahmed; Abuelhamd, Walaa A.; Shahin, Walaa; Nazeer, Marian; Aly, Hany (Journal of Pediatric Genetics, 2020)
To evaluate the role of erythrocyte complement receptor 1 (ECR1) gene in the predisposition to respiratory distress syndrome (RDS), we studied 50 infants with RDS and 50 controls. Real-time polymerase chain reaction allelic discrimination analysis of A3650G (rs2274567) and genotyping of the alleles (HindIII) were performed. Allele L of HindIII restricted single nucleotide polymorphism (SNP) associated with the severity of RDS. Duration of oxygen and ventilation in genotypes AA and AG of A3650G SNP was longer than genotype GG (17.6 ± 19.4 and 8.6 ± 4.5 days, p = 0.01) and (8.9 ± 11.9 and 3.9 ± 3.53 days, p = 0.03), respectively. A3650G and HINDIII digested gene polymorphisms of ECR1 may be of little importance for RDS.
Keywords: Ecr1; polymorphism; RDS; A3650G SNP